Supervision of Village Fund Management by the Regional Inspectorate of Pamekasan Regency - Ranarosyidah Rihadatul'Asy (CV. Pustaka Parawali, 2025)
In the use of village funds, supervision is needed, supervision of the management of village funds has been carried out in synergy, so that the supervision mechanism is effective and efficient, it is possible to give sanctions to parties who do not implement the provisions as stipulated. This Village Fund is supervised by various parties, from the village community, sub-district head, Village Consultative Body, Government Internal Supervisory Apparatus (APIP), Audit Board of Indonesia, and Corruption Eradication Commission. In addition, it is also supervised by the Ministry of Finance in synergy with the Ministry of Home Affairs and the Ministry of Villages, Disadvantaged Regions and Transmigration. One of the parties that supervises is the Regional Inspectorate. The purpose of this study is to analyze the use of village funds, obstacles and solutions in coaching in the field and analyze efforts made to overcome obstacles in its implementation in the field. The research method is sociological legal research, the approach used in addition to the statutory regulatory approach is the approach by conducting interviews.